JURNAL PENGARUH PENGGUNAAN MODEL PEMBELAJARAN JIGSAW TERHADAP KARAKTER SISWA DI KELAS XI SMA NEGERI 6 PADANGSISIMPUAN - Emmi Juwita Siregar (Jurnal Education and Development, 2019)
The study aims to see how far the picture is whether there is a significant influence through the use of the Jigsaw Learning Model on the Character of Class IX Students of SMA Negeri 6 Padangsidimpuan 6. Research has carried out during April-June 2019 at SMA Negeri 6 Padangsidimpuan. Research method has been applied is the experimental method. The population that has been used in this study is all students of class XI 6 Padangsidimpuan State High School as many as 1 class, totaling 31 people. Sampling technique used is total sampling, where the total population is 31 people. In accordance with the results of the calculation of descriptive analysis, the value of the Jigsaw Learning model is 88.84 included in the "Good" category. Then the student character results before using the Jigsaw learning model with an average value of 0.37 included in the "Low" category, the "High" result is inferential analysis using SPSS 22 aided by a Paired Sample Test-assisted type of test through assumptions, but if the sig < 0.05, then the hypothesis is accepted, meaning that there is an influence of the use of Jigsaw learning models on the character of XI students of SMA 6 Padangsidimpuan.